2017
DOI: 10.1093/cid/cix277
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improving Early Diagnosis of Congenital Chagas Disease in an Endemic Setting

Abstract: Summary: Congenital Trypanosoma cruzi transmission is now estimated to account for 22% of new infections. Though the proportion of T. cruzi infected infants with clinical signs has fallen from the 1990s, but symptomatic congenital Chagas disease still represents a significant, albeit increasingly challenging to detect, public health problem. 3 AbstractBackground: Congenital Trypanosoma cruzi transmission is now estimated to account for 22%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 26 publications
3
62
0
1
Order By: Relevance
“…34 A more recent study of 487 infants of T. cruzi infected mothers in Bolivia found higher numbers of false positive and borderline qPCR results. 38 Another recent study found 20.0% positive PCR on cord blood among T. cruzi seropositive mothers in Guanajuato, Mexico. 7 In Argentina, PCR positive rates as high as 30.8% in Jujuy and 27.2% in Formosa have been recently reported.…”
Section: Discussionmentioning
confidence: 97%
“…34 A more recent study of 487 infants of T. cruzi infected mothers in Bolivia found higher numbers of false positive and borderline qPCR results. 38 Another recent study found 20.0% positive PCR on cord blood among T. cruzi seropositive mothers in Guanajuato, Mexico. 7 In Argentina, PCR positive rates as high as 30.8% in Jujuy and 27.2% in Formosa have been recently reported.…”
Section: Discussionmentioning
confidence: 97%
“…In the same two birth cohorts, the frequency of low birthweight, low Apgar scores, mortality and other clinical signs also fell significantly among uninfected infants, regardless of maternal infection status, suggesting that improvements in prognosis may have been related, at least in part, to advances in prenatal care and nutrition [20]. In a later Bolivian cohort of births from 2010-2014, 22% of T. cruzi-infected singletons had low birthweight compared to 8% of infants of uninfected mothers [18]. Twenty-nine percent of infected infants had one or more manifestations consistent with congenital Chagas disease; no severe morbidity or mortality due to T. cruzi infection was observed.…”
Section: Clinical Manifestations Of Congenital Chagas Diseasementioning
confidence: 94%
“…Data from prospective and retrospective observational studies as well as case reports are often interpreted interchangeably. Completeness of detection, and therefore measured incidence, will differ based on the number, type and timing of infant specimens, sensitivity of diagnostic methods and rates of follow-up at 9 months or later [17,18]. Nevertheless, factors shown to be associated with higher risk of congenital transmission include younger maternal age (believed to reflect more recent infection) [19,20], maternal and neonatal immunological responses [21,22], higher maternal parasitaemia [19,23], twin births [19], and HIV co-infection [24,25].…”
Section: Congenital Trypanosoma Cruzi Transmissionmentioning
confidence: 99%
See 2 more Smart Citations